An Analysis of Students’ Problem in Writing Recount Text - Mezia Kemala Sari (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2017)
This research aims at finding the writings’ problem written by students in writing recount text. This descriptive research is qualitative. The choosen respondent is first semester students in Educational English Program at FKIP UMSB in Padangpanjang which consist of one class. Technique in collecting data is total sampling of ten students and analized due to the document analysis. The analysis guide has been formulated as students’ writing problem indicators in writing recount text which consist of Capitalization, Punctuation, Inexpliciteness/Fuziness, Poor Organization/Illogical Sequence, Spelling And Grammatical Errors. From the document checklist, the result shows that the problem that mostly occur is Capitalization (32%) followed by Punctuation (24%) and also Inexpliciteness/fuziness problem (20%). Then Poor organization/illogical sequence (12%), Spelling (8%). while grammatical error occurs in less percentage (4%).It shows that students need more basic skills in order to improve their writing comprehension. Keywords: Writing Problem, Writing Analysis, Recount Text.